2014
DOI: 10.1386/ijcm.7.2.205_1
|View full text |Cite
|
Sign up to set email alerts
|

Metal made me who I am: Seven adult men reflect on their engagement with metal music during adolescence

Abstract: The relationship between adolescent mental health and their habits of music listening with regard to metal music has been consistently explored in academic research since the rise in popularity of heavy metal in the late 1970s and early 1980s. Correlational studies have been most prominent, but do not tend to explore this relationship in the depth required to garner a detailed understanding of the nature of this music engagement. The aim of this study was to investigate adolescent experiences of metal music fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
(34 reference statements)
2
19
0
1
Order By: Relevance
“…The data also suggested possible benefits of subculture affiliation, including the sense of acceptance and belonging that can come from being part of a subculture. This mirrors findings from the wider literature on alternative subcultures (Hines & McFerran, ; Munsell, ). Data suggested that self‐harm was at times seen as a part of the Emo subculture, but this did not seem as strong a theme, more apparent in Trnka et al .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The data also suggested possible benefits of subculture affiliation, including the sense of acceptance and belonging that can come from being part of a subculture. This mirrors findings from the wider literature on alternative subcultures (Hines & McFerran, ; Munsell, ). Data suggested that self‐harm was at times seen as a part of the Emo subculture, but this did not seem as strong a theme, more apparent in Trnka et al .…”
Section: Resultssupporting
confidence: 81%
“…These mediating mechanisms clearly require further investigation. It should also be noted that there is evidence of the positive effects of subculture affiliation, in terms of a sense of belonging and community (Hines & McFerran, ; Munsell, ; Young et al ., ). Well‐designed longitudinal qualitative studies may be valuable here in examining possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[33] pokazuje, że preferowanie "mocnej muzyki" łączy się z ujawnianiem myśli samobójczych czy samookaleczeń słuchaczy. Inne badania wskazują na istnienie korzyści ze słuchania tego rodzaju muzyki: słuchacze ci przejawiają niższy poziom lęku i mają mniej objawów depresji [34] oraz większą motywację, pobudzenie, pewność siebie czy samoakceptację [35]. Gordon i wsp.…”
Section: Grupa Badanaunclassified
“…The success of change process research in APs is dependent upon understanding and defining the variables involved. Traditionally, this has been conceptualised as the relationship between the therapist, arts form, patient and the dynamics and the themes that occur, which together amount to a therapeutic narrative (Cassidy, Turnbull, & Gumley, 2014;Greenwood, 2012;Hines & McFerran, 2014;Huss, 2009;Koch & Fischman, 2011;McFerran & Wigram, 2005). This in itself informs a change hypothesis, but in art psychotherapy case study research the sequential observable actions of the therapist are rarely described and tested against a hypothesis of what might be changing for the patient in clinical work, and why the changes have occurred.…”
Section: Introductionmentioning
confidence: 99%